2021
DOI: 10.1029/2021gh000383
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Air Pollution and COVID‐19 Pandemic: An Investigation in Mumbai, India

Abstract: Spatial hot-spots of COVID-19 infections and fatalities are observed at places exposed to high levels of air pollution across many countries. This study empirically investigates the relationship between exposure to air borne pollutants i.e. sulphur dioxide, nitrogen dioxide and particulate matter (SO2, NO2 and PM10) and COVID-19 infection and death at the smallest administrative level (ward) of Mumbai city in India. The paper explores two hypothesises -COVID-19 infection is associated with air pollution and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 53 publications
0
10
0
1
Order By: Relevance
“…Even though these areas are structured as a ward, all 55 wards individually satisfied one of the conditions for Census Town, framed by the Census Office, Government of India, of having at least 400 people per square kilometer (Cyriac & Firoz, 2022; Jain & Korzhenevych, 2020). The actual population density of this city is 4089 people per square kilometer, which is five times lower than Mumbai, the densest city in the country, with a range of 21,000 people per square kilometer (Chattopadhyay & Shaw, 2021; Shahfahad et al, 2022). As stated initially, 13 city wards do not have space for slums and informally settled dwellings.…”
Section: Resultsmentioning
confidence: 94%
“…Even though these areas are structured as a ward, all 55 wards individually satisfied one of the conditions for Census Town, framed by the Census Office, Government of India, of having at least 400 people per square kilometer (Cyriac & Firoz, 2022; Jain & Korzhenevych, 2020). The actual population density of this city is 4089 people per square kilometer, which is five times lower than Mumbai, the densest city in the country, with a range of 21,000 people per square kilometer (Chattopadhyay & Shaw, 2021; Shahfahad et al, 2022). As stated initially, 13 city wards do not have space for slums and informally settled dwellings.…”
Section: Resultsmentioning
confidence: 94%
“…High temperatures (Sasikumar et al., 2020 ) and air pollution concentrations (Chattopadhyay & Shaw, 2021 ) have been related to COVID‐19 spread and deaths, respectively. Therefore, we included these factors in the model and temperature was found to have a negative relation to number of doses applied and mobility index.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have seen that various MH cities have undergone significant changes in PM 2.5 levels that could trigger the outbreak of COVID-19 and make this state a hotspot in India. Generally, MH states experienced unhealthy as well as very poor air quality (Chattopadhyay and Shaw 2021 ); Bashir et al ( 2020 ) and Fattorini and Regoli 2020 ) showed how air polluted areas become COVID hotspots during this time. Hence, MH faced devastating consequences of it.…”
Section: Discussionmentioning
confidence: 99%